OF INTERPRETATION - Dibakar Pal (European Scientific Journal, ESJ, 2015)
Interpretation is to explain the meaning of something mysterious or abstruse to make understandable. It may be foreign words, a speech, a poem, data, evidence, a difficult text, an inscription, a dream, etc. It is to have or show one’s own understanding of the meaning of something in question. It makes one happy if the meaning favors him. Then the person judges the meaning as per his sweet will or knowledge and intellect and takes decision accordingly. Thus he is self-guided. Also he is self imprisoned simultaneously. On the other hand a fool moves mechanically at the beckon of a stranger. He is so born free. He wants to please everybody. He is whimsical. He cares if he likes. He cares not if he likes not. For, he has no base and no brake at all. As such a wise person opines that it is better to experience loss than to gain through third party’s guidance. Beauty or complexion is interpreted differently by different people. It is just like various food habits of different communities. Choice of one may not be accepted by another one. This is very important in case of selecting life-partner. So everybody should select the life-partner based on self judgment. Here third party’s involvement or interpretation invites problem. In some society guardian selects the bride or groom. In such a case judicious parents take clearance from their son or daughter before taking any final decision. Some face has universal face value. In that case they need no interpretation. Similarly, love at first sight needs neither introduction nor interpretation. However, both appropriate interpretation and interpreting appropriation are very crucial factors.